Tonsillectomy rates in the South African private healthcare sector - Douglas-Jones, Paul (Division of Otorhinolaryngology, 2018)
Background. Adeno-/tonsillectomy is a commonly performed procedure with internationally standardised and recognised indications. Despite this, there exists considerable international (190 - 850/100 000 people ≤19 years of age) and regional variation in adeno-/tonsillectomy rates. This variation has been ascribed to differences in clinical practice and referral patterns, as well as social and family factors, rather than differences in clinical need or regional morbidity. Objectives. To describe the adeno-/tonsillectomy rate in the South African private healthcare sector, and regional variations thereof. To compare local rates with international rates and to assess current trends in adeno-/tonsillectomy clinical practice. Methods. Analysis of adeno-/tonsillectomy data from January 2012 to December 2013, provided by the largest South African private healthcare funder, accounting for 31% of the medical scheme market. Rates are expressed per 100 000 people ≤19 years of age. Results. The tonsillectomy rate in the South African private healthcare sector was 1888/100 000 people ≤19 years of age in 2012. In 2013, the rate dropped significantly (p-value <0.001) to 1755/100 000. Both are more than double the highest national tonsillectomy rate reported in the literature. There was also considerable regional variation in the adeno-/tonsillectomy rate within South Africa. Otorhinolaryngologists are responsible for approximately 80% of adeno- /tonsillectomies performed in the South African private healthcare sector. Discussion. The South African tonsillectomy rate is very high when compared to international trends and varies regionally within the country. The literature does not support an increased burden of disease as the reason behind this. Rather, it is differences in training and clinical practice of clinicians, as well as social and family factors that have been implicated. Conclusion. The adeno-/tonsillectomy rate in the South African private healthcare sector is substantially higher than international norms. The reasons for this discrepancy require further consideration and investigation.